2015
DOI: 10.1016/j.compag.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry cultivar identification and quality evaluation on the basis of multiple fruit appearance features

Abstract: The appearances of agricultural  products are important indices for evaluating the quality of commodities and the characteristics of different varieties. In general, the appearances are evaluated by experts based on visual observations. However, the concern regarding this method is that it lacks objectivity, and it is not quantifiable because it depends greatly on an empirical knowledge. In addition, agricultural products have multiple appearance features; therefore, several of them need to be analyzed simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Strawberries of differing cultivars were able to be distinguished by all appearance, aroma, and flavor attributes, excluding fermented and floral aroma, as well as firmness and astringency. This is supported by previous research indicating differences between cultivars in both sensory and quality properties (Du et al, ; Fernández‐Lara et al, ; Gündüz, ; Šamec et al, ; Yamamoto et al, ). Appearance attributes have been previously demonstrated as distinguishing cultivars (Yamamoto et al, ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Strawberries of differing cultivars were able to be distinguished by all appearance, aroma, and flavor attributes, excluding fermented and floral aroma, as well as firmness and astringency. This is supported by previous research indicating differences between cultivars in both sensory and quality properties (Du et al, ; Fernández‐Lara et al, ; Gündüz, ; Šamec et al, ; Yamamoto et al, ). Appearance attributes have been previously demonstrated as distinguishing cultivars (Yamamoto et al, ).…”
Section: Resultssupporting
confidence: 87%
“…This is supported by previous research indicating differences between cultivars in both sensory and quality properties (Du et al, ; Fernández‐Lara et al, ; Gündüz, ; Šamec et al, ; Yamamoto et al, ). Appearance attributes have been previously demonstrated as distinguishing cultivars (Yamamoto et al, ). In addition to this, research indicates that esters, furanones, and lactones are volatiles that fluctuate in strawberries dependent upon the cultivar (Dong et al, ; Larsen & Poll, ; Latrasse, ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…validation of methodology with real foods Fatih TARLAK 1 with the computer vision system is the best way to measure the colour of food products, which have non-homogenous colour, and the system could be used for classification and prediction of chemical properties of foods. Recently, Yamamoto et al (2015) have demonstrated that qualitative evaluation of the appearance of strawberries can be achieved based on a computer vision analysis technique.…”
Section: Introductionmentioning
confidence: 99%